Extended Design Science Research Methodology For Parallel Vision System - Dewi, Deshinta Arrova; Sundararajan, Elankovan (International Journal of Engineering and Technology, 2018)
Vision system implements image processing in its design and development. The process involves a series of static and dynamic images that are received from a real-time environment. The vision system produces an important outcome in term of object features that are meant for observation, for example, object location, identity, orientation, and others. The previous research in image processing has incorporated a test-driven agile simulation as a research methodology. However, the research methodology for the vision system remains lack of attention. This paper investigates the possibility of the Design Science Research Methodology (DSRM) for vision system application. First, the vision system framework that involves image processing is presented. Second, qualitative content analysis to find a match between vision and DSRM components is demonstrated. Third, investigation on the parallelization of the vision system is reviewed and finally, the extension of DRSM to accommodate parallelization is exposed.Â  The selected case study in this paper involves a vision system for an autonomous robot whereby a parallelization is employed to accelerate computation. The analysis shows that the customized DSRM match with the parallel vision system development stages. The customized DRSM will assist the vision engineers to design the vision system efficiently.